Effects on birth weight of smoking, alcohol, caffeine, socioeconomic factors, and psychosocial stress. - Brooke, O. G. (1989)
OBJECTIVE--To investigate the effects of smoking, alcohol, and caffeine consumption and socio-economic factors and psychosocial stress on birth weight. DESIGN--Prospective population study. SETTING--District general hospital in inner London. PARTICIPANTS--A consecutive series of 1860 white women booking for delivery were approached. 136 Refused and 211 failed to complete the study for other reasons (moved, abortion, subsequent refusal), leaving a sample of 1513. Women who spoke no English, booked after 24 weeks, had insulin dependent diabetes, or had a multiple pregnancy were excluded. MEASUREMENTS--Data were obtained by research interviewers at booking (general health questionnaire, modified Paykel's interview, and Eysenck personality questionnaire) and at 17, 28, and 36 weeks' gestation and from the structured antenatal and obstetric record. Variables assessed included smoking, alcohol consumption, caffeine consumption, and over 40 indicators of socio-economic state and psychosocial stress, including social class, tenure of accommodations, education, employment, income, anxiety and depression, stressful life events, social stress, social support, personality, and attitudes to pregnancy. Birth weight was corrected for gestation and adjusted for maternal height, parity, and baby's sex. MAIN RESULTS--Smoking was the most important single factor (5% reduction in corrected birth weight). Passive smoking was not significant (0.5% reduction). After smoking was controlled for, alcohol had an effect only in smokers and the effects of caffeine became non-significant. Only four of the socioeconomic and stress factors significantly reduced birth weight and these effects became non-significant after smoking was controlled for. CONCLUSIONS--Social and psychological factors have little or no direct effect on birth weight corrected for gestational age (fetal growth), and the main environmental cause of its variation in this population was smoking.